First-principles calculations to investigate magnetic and thermodynamic properties of new multifunctional full-Heusler alloy Co2TaGa - Ayad, M.; Belkharroubi, F.; Boufadi, F. Z.; Khorsi, M.; Zoubir, M. K.; Ameri, M.; Ameri, I.; Al-Douri, Y.; Bidai, K.; Bensaid, D. (Indian journal of physics, 2020)
The structural, elastic, electronic, magnetic and thermodynamic properties of Co 2 TaGa full-Heusler alloy are investigated using density functional theory-based full-potential linearized augmented plane waves method. Our results present Co 2 TaGa full-Heusler in CuHg 2 Ti-type structure FM phase that is mechanically and dynamically stable at pressure. The negative formation energy of Co 2 TaGa is −1.516 eV that can be synthesized experimentally. The electronic properties of 3 d transition metal-based full-Heusler compound Co 2 TaGa are calculated within Perdew–Burke–Ernzerhof generalized gradient approximation. Co 2 TaGa is predicted to be half-metallic ferrimagnet with an indirect band gap and 100% spin polarization. The calculated total magnetic moment is 2 μ B , which is mainly determined by Co partial moment, and total spin magnetic moment is in conformity with Slater–Pauling rule Mt that gives a simple function of valence electrons number, Zt, formulated as Mt = Zt − 18.